Burning Issues: mlk revisited - Frendo, Anthony J. (Journal of Semitic studies, 2016)
Basing themselves on Otto Eissfeldt’s 1935 work on the Phoenician-Punic sacrifice known as molk , many biblical scholars followed in his footsteps and opted to substitute the biblical deity Mōleḵ in the Hebrew Bible with this sacrificial term. However there always were other scholars who disagreed with this position. Recently there has been a renewed surge of interest in the problem as to whether the Carthaginians had literally burnt their children in sacrifice to their gods. This problem touches on related issues found in the Hebrew Bible, and it makes it necessary to look again at some biblical texts to see whether children in ancient Israel were indeed sacrificed by burning. When the various ways of vocalizing the Semitic word mlk with its basic meaning of ‘king’ are taken into account alongside the fact that in West Semitic there are words which can be used either as the names of deities or simply as their epithets, it becomes more plausible to hold that, although the biblical word ‘Mōleḵ’ does indeed refer to a deity, in a number of texts it was most probably originally vocalized as meleḵ and used as an epithet with reference to different gods including Baal and Yahweh himself. Indeed, we even encounter composite divine names, one component of which functions as an epithet. Often it was idolatrous child sacrifice that was condemned in the Hebrew Bible and not the sacrifice of children made to Yahweh, even when the latter rite was performed at the Topheth in the Valley of Hinnom. However, it seems that there was also a non-Tophet group in Israel, which condemned the sacrifice of children tout court whether offered to Yahweh or to foreign deities, and this is reflected in certain texts, such as Deuteronomy.